Utility of the PANC 3 score as a predictor of severity in patients with acute pancreatitis - Abanto Lou, Patricia (2021)
Objective: To demonstrate that the PANC 3 score is useful as a predictor of severity in patients with acute pancreatitis. Materials and methods: Retrospective, observational study of diagnostic test type carried out in the Gastroenterology service in the Hospital Regional Docente de Trujillo which included a total of 160 patients with acute pancreatitis. Sensitivity, specificity, PPV and NPV of the PANC 3 score were calculated. Results: The PANC 3 score showed a sensitivity of 73.08%, a specificity of 100%, a positive predictive value of 100% and a negative predictive value of 95.04%. Pleural effusion proved to be the best parameter predicting severity in patients with acute pancreatitis, with a sensitivity of 88.46% and a specificity of 89.55%. The male genre is associated with severe acute pancreatitis. Conclusions: The PANC 3 score can be used as a predictor of severity in patients with acute pancreatitis.